2007
DOI: 10.1080/09658210701701394
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and the self-reference effect in memory

Abstract: The present study investigates potential age differences in the self-reference effect. Young and older adults incidentally encoded adjectives by deciding whether the adjective described them, described another person (Experiments 1 & 2), was a trait they found desirable (Experiment 3), or was presented in upper case. Like young adults, older adults exhibited superior recognition for self-referenced items relative to the items encoded with the alternate orienting tasks, but self-referencing did not restore thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
129
3
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(161 citation statements)
references
References 48 publications
(75 reference statements)
25
129
3
4
Order By: Relevance
“…Medial prefrontal cortex is critical to the processing of self-relevant information in that increased engagement of the region during encoding distinguishes items later remembered from those later forgotten . Furthermore, selfreferencing improves memory to the same extent for both young and elderly, which suggests that self-referencing operates similarly in both age groups (Gutchess, Kensinger, Yoon, & Schacter, 2007c;Mueller, Wonderlich, & Dugan, 1986). In contrast to the default state literature, these regions are engaged, rather than suppressed or deactivated, during judgments of self-relevance.…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…Medial prefrontal cortex is critical to the processing of self-relevant information in that increased engagement of the region during encoding distinguishes items later remembered from those later forgotten . Furthermore, selfreferencing improves memory to the same extent for both young and elderly, which suggests that self-referencing operates similarly in both age groups (Gutchess, Kensinger, Yoon, & Schacter, 2007c;Mueller, Wonderlich, & Dugan, 1986). In contrast to the default state literature, these regions are engaged, rather than suppressed or deactivated, during judgments of self-relevance.…”
contrasting
confidence: 38%
“…Participants judged whether the adjective described them (Self trials), described Albert Einstein (Other trials), or was presented in upper case (Case trials). Albert Einstein was selected as an appropriate target person based on prior work (Gutchess et al, 2007c) that established that young and elderly did not differ in their familiarity with or attitude towards him. Figure 1 presents for each of the three conditions, across two runs in the scanner in an event-related design.…”
Section: Methodsmentioning
confidence: 99%
“…Age differences in making judgments about personality traits in regards to one's self have not been found (Keightley, Winocur, Burianova, Hongwanishkul, & Grady, 2006;Ruby et al, 2009), and the self reference effect in episodic memory is also preserved into older age (Glisky & Marquine, 2009;Gutchess, Kensinger, Yoon, & Schacter, 2007). Although this work suggests that some aspects of self-reference are not markedly altered as we age, some of the other types of related processing, mentioned above, are influenced by aging.…”
Section: Introductionmentioning
confidence: 48%
“…Indeed, in these studies, retrieval performance is better for information that has been encoded in reference to the self than for information that has been processed semantically or in reference to other people. This wellknown cognitive phenomenon, named the Self Reference Effect (SRE; Rogers et al, 1977), is a strong characteristic of human cognition since it has been observed in various populations including healthy older people (Gutchess et al, 2007), with various materials and various paradigms at encoding and recognition and with different designs (for a review see Symons and Johnson, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 99%